Affectivity among students and the system of quotas for black people - Nery, Maria da Penha; Costa, Liana Fortunato (Paidéia (Ribeirão Preto), 2009)
This study focused on affectivity existent between students favored by the quota system and regular students during the period in which racial quotas were adopted by the University of Brasilia. The theoretical reference of this qualitative study was the Jacob Levy Moreno's Socionomy. Sociodrama and semi-structured interviews were used. Five students participated in the sociodrama, three students and one individual from a non-governmental institution were interviewed. Data were analyzed through the qualitative epistemology. We observed that students who were regularly admitted at the university were indifferent to students who were favored by the quota system and disregarded racial issues. There was a high expectation among students admitted through the quotas system to exceed academic performance so to placate discrimination generated by such policy. In regard to identity processes, most students occulted their identity and feared being exposed to this new social role. We conclude that there is a need to create psychosocial projects to integrate students within the affirmative action context.